2020
DOI: 10.35808/ijeba/526
|View full text |Cite
|
Sign up to set email alerts
|

The Hedonic Pricing Model Applied to the Housing Market

Abstract: Purpose:The article applies the hedonic pricing model to estimate house price in the housing market of Vietnam, which is a country with a fledgeling housing market, so the study is expected to bring interesting findings. Design/Methodology/Approach: By applying the hedonic pricing model, most of the previous studies have reported that house price is significantly influenced by the characteristics of the house itself, its location and surrounding facilities. Based on this, the article adopts the Ordinary Least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…The findings of this paper generally reinforce the consensus that property values are influenced by their internal and external attributes: structural, locational and neighbourhood characteristics (see for example Brett et al, 2003;Kieti and Ogolla, 2021;McCluskey and Borst, 2007;Thanasi, 2016). Several studies, for instance, have found apartment size to be the most significant factor influencing its value positively (see Ahmed and Yacim, 2018;Belete and Yilma (2020);Nguyen, 2020;Randeniya et al (2017);Thanasi, 2016;Sirmans et al, 2005, amongst other studies). Similarly, location (usually measured in distance from the CBD) has been identified by most existing studies as an important variable negatively influencing property values (see for example Ayan and Erkin (2014); Ferlan et al (2017); Frew and Wilson, 2002;McCluskey and Borst, 2007;Randeniya et al (2017); Oduwole andEze, 2013, Ottensmann et al, 2008, amongst others).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The findings of this paper generally reinforce the consensus that property values are influenced by their internal and external attributes: structural, locational and neighbourhood characteristics (see for example Brett et al, 2003;Kieti and Ogolla, 2021;McCluskey and Borst, 2007;Thanasi, 2016). Several studies, for instance, have found apartment size to be the most significant factor influencing its value positively (see Ahmed and Yacim, 2018;Belete and Yilma (2020);Nguyen, 2020;Randeniya et al (2017);Thanasi, 2016;Sirmans et al, 2005, amongst other studies). Similarly, location (usually measured in distance from the CBD) has been identified by most existing studies as an important variable negatively influencing property values (see for example Ayan and Erkin (2014); Ferlan et al (2017); Frew and Wilson, 2002;McCluskey and Borst, 2007;Randeniya et al (2017); Oduwole andEze, 2013, Ottensmann et al, 2008, amongst others).…”
Section: Discussionsupporting
confidence: 85%
“…The level of amenities and services has always been determined to have a positive influence on property values as they are likely to enhance the utility of the consumer. The provision of a shared swimming pool and the gym has been found to have a positive influence on apartment values elsewhere (Kieti and Ogolla, 2021;Nguyen, 2020;Sirmans et al, 2005). The existing research has also established that quality floor finishes have positive affection on property values (Nguyen et al, 2020;Thanasi, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations